Case Report: Advanced pulmonary sarcomatoid carcinoma with adrenal gland metastasis after sintilimab combined with anlotinib treatment - Dai, Gangyi; He, Lang; Yan, Qin; Li, Yamao; Huang, Yuandong; Li, Bin; Wang, Guoping (Frontiers in Oncology, 2023)
Background Pulmonary sarcomatoid carcinoma (PSC) is a rare subtype of non-small-cell lung cancer (NSCLC), which is resistant to conventional chemotherapy and radiotherapy with a poor prognosis. The MET inhibitor may be effective for the patients with MET exon 14 skipping mutation. This mutation was not detected in this patient. However, the PD-L1 TPS 60%, KRAS and TP53 mutations were detected in this patient could benefited from immunotherapy. The anlotinib is a novel multitarget antiangiogenic drug that could be effective for advanced non-small-cell lung cancer and some sarcoma patients. We report a patient with advanced pulmonary sarcomatoid carcinoma successfully treated with immunotherapy combined with antiangiogenic drugs. Case summary A 75-year-old male was admitted to the hospital in July 2020 because of productive cough for more than three months. The patient was diagnosed with advanced pulmonary sarcomatoid carcinoma with adrenal gland metastasis (cT4N3M1b, stage IVA) was treated in our hospital. Genetic testing revealed KRAS P.L19F mutation (abundance 19.12%) and NFEE2L2 P.E82G mutation (abundance 14.84%); TP53 P.S183 mutation (abundance 26.97%), TMB(Tumor Mutational Burden) 30.91 muts/Mb, MSS, and PD-L1 (Daco 22C3) TPS 60% were also detected. We administrated sintilimab combined with anlotinib treatment, a PD-1 inhibitor with antiangiogenic drug. The patient achieved a favorable outcome with tolerable adverse effects. Conclusion Sintilimab combined with anlotinib treatment may lead to a favorable outcome for patients with advanced pulmonary sarcomatoid carcinoma.